FIGURATIVE LANGUAGE IN SONGS “IF I WERE A BOY” AND “FIREWORK” AS LEARNING MATERIAL FOR SENIOR HIGH SCHOOL: FIGURATIVE LANGUAGE IN SONGS “IF I WERE A BOY” AND “FIREWORK” AS LEARNING MATERIAL FOR SENIOR HIGH SCHOOL - Henryani, Silvi; Perpisa, Lili; Syafar, Dian Noviani (Teaching English as Foreign Language, Literature and Linguisticss, 2022)
Figurative language is language which employs various figures of speech. This research discusses about figurative language in songs “If I were a Boy” and “Firework” as learning material for Senior High School. The purpose of this research is to find the contextual meaning and the types of figurative language used in Beyonce and Katy Perry found in learning material for grade XI. The source of data was taken from the lyrics of Beyonce and Katy Perry song. The research design used in this research is qualitative research with a document or content analysis as the research type. The research described types of figurative language and contextual meaning from Beyonce and Katy Perry song. From the analysis, there were seven types of figurative languages: they were Simile, Personification, Hyperbole, Metaphor, Imagery, Onomatopoeia, and Alliteration. To supports the analysis, some types of figurative language and other related references were used. There were also some related theories about figurative language used to support the analysis. Based on the results of data analysis it was found that, there were 2 Metaphor, 2 Imagery, 6 Hyperbole, 5 Simile, 4 Alliteration,1 onomatopoeia, and 1 Personification. Then the type of figurative language were classified and analyzed. This research is highly expected to give contribution for the reader to know about figurative language clearly. It can help the reader know contextual meaning and speak English fluently. And it can also be expected to enrich new English vocabulary used in the daily conversation.